STRUCTURAL-SEMANTIC AND LINGUACULTURAL ANALYSIS OF PHRASEOLOGICAL UNITS WITH PHYTONYM COMPONENT IN ENGLISH AND UZBEK LANGUAGES (World Bulletin of Social Sciences, 2022)
The problem of studying phytonymic phraseology is especially relevant, because phytonyms play a significant role in human life, not only in decorative and aesthetic refraction, but also participate in the transmission religious, symbolic, aesthetic and mythological representations. The use of phytonymic phraseological units in speech is very essential, since their study introduces students to cultural component in terms of language learning. Phytonymic phraseology most clearly and accurately reflects the spirit people, cultural and historical experience of knowing the world, as well as its national mentality, due to its expressiveness and emotionality. In this article, there are information about structural-semantic and linguacultural analysis of phraseological units with phytonym component in English and Uzbek languages